(untitled) (Medical Forum Monthly, 2024)
Objective: To investigate the efficacy of intravenous nalbuphine in managing post anesthesia shivering. Study Design: Cross sectional Place and Duration of Study: This study was conducted at the Anesthesia department of Lady Reading Hospital, Peshawar from January 2022 to December 2022. Methods: A total of 60 patients who were planned for surgery under anesthesia were enrolled. Patients were divided into two groups. Group Nalbuphine: Patients in this group received nalbuphine at a dose of 0.08 mg/kg, administered via the intravenous (IV) route. The nalbuphine was mixed with 5 mL of saline. Group placebo: This is the control group, where patients received only saline (5 mL) via the IV route. Results: After 5 minutes of treatment, nalbuphine was effective more than placebo, 70.0% and 10.0%, respectively. (p<0.001). After 15 minutes of treatment, nalbuphine was more effective than placebo, 70.0% and 6.7%, respectively. (p<0.001). Similarly, after 30 minutes of treatment, nalbuphine was most effective than placebo 80.0% and 20.0%, respectively. (p<0.001). Conclusion: The intravenous administration of nalbuphine, a kappa-receptor agonist provides potent antishivering effect on the peripheral nervous system. Nalbuphine can be used in post anesthesia shivering in different surgeries.